The Influence Of Lifestyle, Brand Image And Brand Equity On The Purchase Decision Of Thrift Store In Yogyakarta - Lingga, Bakas Anja; Lukatiningsih, Ambar; Maharani, Bernadetta Diansepti (Kontigensi : Jurnal Ilmiah Manajemen, 2024)
This study aims to determine the influence of lifestyle, brand image, and brand equity on the purchase decision of thrift stores in Yogyakarta. The study population and sample consisted of 70. Data collection is carried out through the use of questionnaires; this method will be used by researchers to obtain data on the influence of lifestyle, brand image, and brand equity on thrift store purchase decisions in Yogyakarta. Furthermore, classical assumption tests such as normality, heteroscedasticity, and multicollinearity are carried out to ensure the suitability of the data with the assumptions required in regression analysis. The hypothesis results were obtained from analysis using T, F, and R2 tests using SPSS software version 23. From these results, it was concluded that lifestyle variables had no effect on the decision to purchase Thrift Store in Yogyakarta, brand image variables had a positive and significant effect on the decision to purchase Thrift Store in Yogyakarta, variable brand equity had a positive and significant effect on Thrift Store in Yogyakarta. Variables lifestyle, brand image, and brand equity together effect the purchase decision of Thrift Store in Yogyakarta.